Time for 'software' - Abd Razak, Dzulkifli (2005)
Recently, Islam Hadhari (civilisationa Islam) as a concept received the unanimous support of the National Fatwa. Council as a way forward to make Malaysia more dynamic and progressive (NST, May 7). It is time then to translate the concept into action, as an approach that emphasises development, consistent with the tenets of Islam, like many other belief systems, through the mastery of knowledge. Indeed, among the 10 principles of Islam Hadhari, seeking knowledge and education is strongly featured. Others include good governance, a balanced economy, justice and trustworthiness, care for the environment, care for the minority and women, cultural and moral integrity, good quality of life, and strong defences. In fact, none of these can be achieved if education remains a onetrack, monochromatic orthodoxy.